2019
DOI: 10.1021/acsomega.9b00486
|View full text |Cite
|
Sign up to set email alerts
|

Salt-Tolerant Superabsorbent Polymer with High Capacity of Water-Nutrient Retention Derived from Sulfamic Acid-Modified Starch

Abstract: The application of superabsorbent polymers (SAPs) is hindered because their absorption capability is greatly affected by the electrolytes in a solution. A novel modified water-absorbent polymer was fabricated by solution polymerization of sulfamic acid-modified starch and acrylic acid; the swelling ratios of this absorbent polymer were 1026 g/g in deionized water and 145 g/g in 0.9% sodium chloride solution and increased by 99.5 and 13.4%, respectively, when compared with ordinary starch-grafted acrylic SAPs. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(22 citation statements)
references
References 38 publications
0
16
0
Order By: Relevance
“…Salinity impairs water absorption because hydrophilic groups of hydrogels bind to salts, blocking water ingress. Salts also suppress the electrostatic interactions among the polymer and water molecules (Xiong et al, 2018;Zhao et al, 2019). Andry et al, 2009 also observed that hydrophilic polymers can exhibit thermal sensitivity.…”
Section: Introductionmentioning
confidence: 97%
“…Salinity impairs water absorption because hydrophilic groups of hydrogels bind to salts, blocking water ingress. Salts also suppress the electrostatic interactions among the polymer and water molecules (Xiong et al, 2018;Zhao et al, 2019). Andry et al, 2009 also observed that hydrophilic polymers can exhibit thermal sensitivity.…”
Section: Introductionmentioning
confidence: 97%
“…The addition of SAP can lead to a reduction in the evaporation and out‐filtration of water from the surface of the soil, and can also improve the soil porosity as well as the stability of the soil structure, 2 thereby, leading to an overall improvement in the efficiency of water utilization. For instance, the widely used biomass‐based SAP materials are attributed to good biocompatibility and excellent degradability 3 .…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, of interest are effective approaches to improve their salt-tolerance, mechanical properties, and degradability, such as introduction of kaolin and bentonite to enhance mechanical performance of PAA or PAM polymers [ 7 , 11 ]. The nature polymers can be introduced into the cross-linked copolymer systems of AA or AM [ 8 ], such as cellulose [ 12 ], natural rubber [ 13 ], starch [ 14 , 15 ] and chitosan [ 16 ], to improve the degradability, biocompatibility and environmental friendliness. However, SAPs based on natural polymers, such as cellulose, starch and chitosan, are prone to degradation resulting in a short cycle of nutrient release and relatively low slow-release performance [ 17 ], and suffer from low water absorption rate, thus have to be used in larger amounts.…”
Section: Introductionmentioning
confidence: 99%